2022
DOI: 10.1002/pc.27208
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoparticle fillers on glass fiber/poly‐ether‐ether‐ketone prepreg laser absorbance, thermal conductivity and interlayer performance

Abstract: Aiming at the use of glass fiber reinforced poly‐ether‐ether‐ketone (GF/PEEK) with low laser absorbance in laser assisted tape winding/placement (LATW/LATP), a method for dyeing GF/PEEK prepreg with nanoparticle fillers (NFs) is presented. First, the effects of carbon black (CB) and graphite (G) NFs on composites laser absorbance and reflection pattern were quantified, and the complex refractive index model was derived. Next, the effects of NFs on composites transverse thermal conductivity were tested, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For instance, Shtein et al, manufactured graphene nanoplatelet/epoxy composites by utilizing a centrifugal mixing approach and obtained a thermal conductivity value of 12.4 W/(m.K), an enhancement of 6800% at a filler loading of 20 vol% when compared to neat polymer 7 . Similarly, Li et al, demonstrated that the addition of graphite at a loading of 7 wt% in PEEK/glass fiber composites leads to an increment of 11.8% in through‐plane thermal conductivity 5 . In addition to graphene and its species, other inorganic fillers, including alumina, 8 aluminum nitride, 9 and boron nitride, 4,10–12 have also been reported for developing thermally conductive polymer composites.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, Shtein et al, manufactured graphene nanoplatelet/epoxy composites by utilizing a centrifugal mixing approach and obtained a thermal conductivity value of 12.4 W/(m.K), an enhancement of 6800% at a filler loading of 20 vol% when compared to neat polymer 7 . Similarly, Li et al, demonstrated that the addition of graphite at a loading of 7 wt% in PEEK/glass fiber composites leads to an increment of 11.8% in through‐plane thermal conductivity 5 . In addition to graphene and its species, other inorganic fillers, including alumina, 8 aluminum nitride, 9 and boron nitride, 4,10–12 have also been reported for developing thermally conductive polymer composites.…”
Section: Introductionmentioning
confidence: 93%
“…To address this bottleneck of low κ, traditionally, metallic, ceramic-based inorganic fillers, or carbon-based fillers with a high intrinsic thermal conductivity and high aspect ratio are incorporated in the host polymer to enhance its heat dissipation properties. [3][4][5][6] For instance, Shtein et al, manufactured graphene nanoplatelet/epoxy composites by utilizing a centrifugal mixing approach and obtained a thermal conductivity value of 12.4 W/(m.K), an enhancement of 6800% at a filler loading of 20 vol% when compared to neat polymer. 7 Similarly, Li et al, demonstrated that the addition of graphite at a loading of 7 wt% in PEEK/glass fiber composites leads to an increment of 11.8% in through-plane thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C p , ρ , and k ∥ are calculated by mixture rule, as shown in (Equation , , ), where Φ is the volume fraction. The relevant measurements and calculations of all data were performed in previous work of 40 Cpitaliccomp=CpitalicGF*ΦitalicGF+CpitalicPEEK*ΦitalicPEEK+CpitalicCB*ΦitalicCB ρitaliccomp=ρitalicGF*ΦitalicGF+ρitalicPEEK*ΦitalicPEEK+ρitalicCB*ΦitalicCB kitaliccomp=kitalicGF*ΦitalicGF+kitalicPEEK*ΦitalicPEEK+kitalicCB*ΦitalicCB …”
Section: Finite Element Modeling and Mechanical Testingmentioning
confidence: 99%
“…The field of composite materials research is extensive and encompasses several relevant applications in science and technology [1][2][3][4][5][6][7]. As a specific type of composite material, photoresponsive polymers have the ability to change physical, chemical, or optical properties when exposed to light [8,9].…”
Section: Introductionmentioning
confidence: 99%